Brain-derived nerve growth factor in the cochlea – a reproducibility study - Brian W. Blakley; Michael Seaman; Abdulrahman Alenezi (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective Brain-derived nerve growth factor (BDNF) plays an important role in cochlear development so it is plausible that it could restore hearing loss if delivered directly into the cochlea. We wished to confirm our previous report that a single intracochlear injection of brain-derived nerve growth factor (BDNF) was beneficial for hearing in guinea pigs. We wished to assess the reproducibility of our results and assess possible improved methods with a view to developing a clinical treatment for sensorineural hearing loss. Methods CDDP was used to create partial hearing loss in 25 guinea pigs. After 30 days the animals underwent ABR testing and unilateral BDNF injection through the round window in one ear and saline injection into the other ear. After allowing possible effects to stabilize, thirty days later, ABR threshold testing was repeated to assess change in threshold. Results Final ABR thresholds were 60–70 dB and were about 11 dB better in the ears treated with BDNF. Conclusion Our original finding that Intracochlear BDNF can improve hearing in guinea pigs was confirmed, but the improvement demonstrated by the methods in this paper is too small for clinical application.